2020
DOI: 10.1021/acsami.0c02647
|View full text |Cite
|
Sign up to set email alerts
|

Light-Excited Antibiotics for Potentiating Bacterial Killing via Reactive Oxygen Species Generation

Abstract: The irrational or excessive use of antibiotics causes the emergence of bacterial resistance, making antibiotics less effective or ineffective. As the number of resistant antibiotics increases, it is crucial to develop new strategies and innovative approaches to potentiate the efficacy of existing antibiotics. In this paper, we report that some existing antibiotics can produce reactive oxygen species (ROS) directly under light irradiation. Thus, a novel antibacterial photodynamic therapy (PDT) strategy is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…Jiang et al reported that some existing antibi-otics, such as polymyxin B, sulfamethizole, norfloxacin, and glycopeptide teicoplanin could directly produce ROS under light irradiation (Figure 5c). [225] Therefore, antibacterial PDT can utilize existing antibiotics at low does, whose cell killing activity is enhanced by light activation. The development of antibiotic-based, antibacterial PDT strategy can effectively kill bacteria using antibiotics.…”
Section: Nanocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al reported that some existing antibi-otics, such as polymyxin B, sulfamethizole, norfloxacin, and glycopeptide teicoplanin could directly produce ROS under light irradiation (Figure 5c). [225] Therefore, antibacterial PDT can utilize existing antibiotics at low does, whose cell killing activity is enhanced by light activation. The development of antibiotic-based, antibacterial PDT strategy can effectively kill bacteria using antibiotics.…”
Section: Nanocatalystsmentioning
confidence: 99%
“…Adapted with permission. [ 225 ] Copyright 2020, American Chemical Society. d) PB@PDA@Ag applied for diabetic wound healing.…”
Section: Applications In Nanomedicinementioning
confidence: 99%
“…The modes of toxicity when designed nanoparticles interact with a bacterium involve disruption of electron transport chains, cell membrane disruption, release of heavy metals, damage of proton efflux pumps, and generation of reactive oxygen species (ROS) [ 20 ]. Among them, ROS has been proved to be a rapid, effective, and broad-spectrum antibacterial and even anti-cancer strategy, and it is not inclined to promote drug-resistant bacteria [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] ]. Moreover, ROS is reactive with DNA and lipids of inactive bacteria, especially to the multidrug-resistant “superbugs” and the refractory biofilms, exhibiting an excellent antibacterial potential [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…ROS can be produced through the catalysis of metals and metal oxides 20,21 , electron transfer in redox reactions, and normal mitochondrial metabolism 22 , etc. Excitation conditions include chemodynamics 23,24 , photodynamics 25,26 and acoustic dynamics 27,28 . The generation of ROS by metal oxide nanosheets often requires external energy stimulation 29,30 .…”
Section: Introductionmentioning
confidence: 99%